Pengembangan Media Berbasis Powerpoint Interaktif Materi Sistem Pencernaan Manusia untuk Siswa Kelas V SD - Zarnaujiah, Nurul Aini; Erwin Rahayu Saputra (Jurnal Sekolah Dasar, 2023)
The purpose of this study was to produce interactive Powerpoint-based learning media for the subject of the human digestive system in natural sciences for 5th grade students at SD Negeri 1 Kalangsari. The method used is R&D (Reseach and Development). The research model used is the ADDIE model, with the stages of analysis, design, development, implementation and evaluation. The subjects used in this study were teachers and grade 5 students at SD Negeri 1 Kalangsari. The results of the study show that interactive PowerPoint-based learning media is very suitable for use in learning the human digestive system for 5th grade elementary school students. This media can also increase students' interest in learning the human digestive system. This interest can be seen from the response of teachers and students after the trial was carried out.